PENGARUH PENGGUNAAN MADU DENGAN PROSES PENYEMBUHAN ULKUS DIABETIKUM PADA PENDERITA DIABETES MELLITUS - Angga Muhti Putra; Yesi Andriani (JURNAL KESEHATAN PERINTIS, 2017)
DM ulcers are sores caused by lack of strong skin elasticity caused by gangrene of the skin of the sugar reaction, causing tissue damage and ulceration in patients with diabetes mellitus (Sudoyo, 2006). DM problems encountered in the field of time the initial survey of patients treated in the Interne Inpatient Space is the case of diabetic ulcers issue on a different degree. Here we can see that the way the ulcer wound treatment using NaCl fluid, there is no therapy that uses liquid honey at room Inpatient Interne Hanafi BC Batusanggkar dr. The purpose of this study is to see Effect of honey on healing of diabetic ulcers in patients with diabetes mellitus in Space Inpatient. The design of this study using Quasi-experimental. The sample in this study determined that as many as 24 patients will be divided into 2 groups: 12 patients in the intervention group performed the act of using honey wound care patients and 12 control group is the group that performed the action wound treatment using 0.9% NaCl and processing data using T test-Independent Based on estimates of the interval can be concluded that 95% believed the average healing of diabetic ulcers in patients with diabetes with treatment using honey ranged from 3.64 to 4.86 and interval estimation Based on the results it can be concluded that 95% believed the average healing of diabetic ulcers in patients with diabetes mellitus with use of NaCl treatment ranged from 1.89 to 3.27. Results of statistical analysis obtained pvalue = 0.001 means that there is a significant effect of the use of honey on diabetic ulcer healing process there are people with diabetes mellitus.It can be concluded that the use of honey is more effective in healing diabetic ulcers. Expected at the hospital for treatment of ulcers can diabetes using natural medicines that can accelerate wound healing in patients with diabetes mellitus